Meta-analyses of clinical neuropsychological tests of executive dysfunction and impulsivity in alcohol use disorder. (2nd January 2017) - Stephan, Rick A.; Alhassoon, Omar M.; Allen, Kenneth E.; Wollman, Scott C.; Hall, Matt; Thomas, William J.; Gamboa, Julia M.; Kimmel, Chrissy; Stern, Mark; Sari, Celina; Dalenberg, Constance J.; Sorg, Scott F.; et al.
ABSTRACT: Background : Promising models for cognitive rehabilitation in alcohol treatment rest on a more nuanced understanding of the associated impairments in the multifaceted domains of executive functioning (EF) and impulsivity. Objectives : This meta-analysis examined the effects of alcohol on the individual subcomponents of EF and impulsivity in recently detoxified participants, including 1) Inhibition & Self-Regulation, 2) Flexibility & Set Shifting, 3) Planning & Problem Solving, 4) Reasoning & Abstraction, and 5) Verbal Fluency. Impulsivity was further examined through an analysis of motor, cognitive, and decisional subcategories. Method : Investigators searched, coded, and calculated effect sizes of impairments demonstrated in a broad range of neuropsychological tests for EF. A total of 77 studies were selected covering 48 years of research with a sample size of 5140. Results : Findings ranged from a Hedges' g effect size of 0.803 for Inhibition to a Hedges' g of 0.359 for Verbal Fluency. Results also varied for the individual subcategories of Inhibition, including a large effect size for decisional impulsivity ( g = 0.817) and cognitive impulsivity (0.860), and a moderate effect size for motor impulsivity ( g = 0.529). The Hayling Test, Wisconsin Card Sorting Test, and Iowa Gambling Task were the measures most sensitive for alcohol effects. Conclusion : Planning, problem solving, and inhibitory abilities are significantly affected by alcohol abuse, with decisional and cognitive forms of impulsivity most impacted. Cognitive remediation targeting these deficits might increase the related functions that mediate the ability to moderate or abstain from alcohol, and so lead to improved treatment results.